Rhabdochona fuscovaria sp. n. (Nematoda: Rhabdochonidae) from the stomach of frog Scinax fuscovarius (Anura: Hylidae) in Brazil - de Alcantara, Edna Paulino; Úngari, Leticia Pereira; Ferreira-Silva, Cristiana; Emmerich, Enzo; Da Silva Pinheiro, Raul Henrique; O´dwyer, Lucia Helena; Da Silva, Reinaldo José (Zootaxa, 2021)
A new nematode species, Rhabdochona (Rhabdochona) fuscovaria sp. n. (Rhabdochonidae), is described based on specimens collected from the stomach of the snouted treefrog Scinax fuscovarius (Hylidae) in the São Sebastião do Paraíso farm, municipality of Boa Esperança do Sul, southeastern Brazil. This species is characterized by deirids small, simple and stylet shaped, prostom funnel-shaped with 14 teeth, conspicuous left spicule (585.7 µm), distal tip slightly widened, moderately dilated, right spicule (132.9 µm), boat-shaped, without dorsal barb at the distal tip, 18 pairs of caudal papillae (9 pairs precloacal and 9 pairs postcloacal), and nonfilamented eggs. This is the fourth species described for South America and the 13th for the Neotropical Region.